CD14 inhibition efficiently attenuates early inflammatory and hemostatic responses in Escherichia coli sepsis in pigs - Thorgersen, Ebbe Billmann (The Federation of American Societies for Experimental Biology, 2010)
Sepsis is a severe infection-induced systemic inflammatory syndrome. Inhibition of downstream inflammatory mediators of sepsis, e.g., TNF-α, has failed in clinical trials. The aim of this study was to investigate the effects of inhibiting CD14, a key upstream innate immunity molecule, on the early inflammatory and hemostatic responses in a pig model of gram-negative sepsis. The study comprised two arms, whole live Escherichia coli bacteria and E. coli lipopolysaccharide (LPS) (n=25 and n=9 animals, respectively). The animals were allocated into treatment (anti-CD14) and control (IgG isotype or saline) groups. Inflammatory, hemostatic, physiological, and microbiological parameters were measured. The proinflammatory cytokines TNF-α, IL-1β, IL-6, and IL-8, but not the anti-inflammatory cytokine IL-10, were efficiently inhibited by anti-CD14. Furthermore, anti-CD14 preserved the leukocyte count and significantly reduced granulocyte enzyme matrix metalloproteinase-9 release and expression of the granulocyte membrane activation molecule wCD11R3 (pig CD11b). The hemostatic markers thrombin-antithrombin III complexes and plasminogen activator inhibitor-1 were significantly attenuated. Anti-CD14 did not affect LPS or E. coli DNA levels. This study documents that CD14 inhibition efficiently attenuates the proinflammatory cytokine response and granulocyte activation and reverses the procoagulant state but does not interfere with LPS levels or bacterial counts in E. coli-induced sepsis.—Thorgersen, E. B., Hellerud, B. C., Nielsen, E. W., Barratt-Due, A., Fure, H., Lindstad, J. K., Pharo, A., Fosse, E., Tønnessen, T. I., Johansen, H. T., Castellheim, A., Mollnes, T. E. CD14 inhibition efficiently attenuates early inflammatory and hemostatic responses in Escherichia coli sepsis in pigs.